Innovation, value-neutrality and the question of politics: unmasking the rhetorical and ideological abuse of evolutionary theory. Issue 2 (3rd May 2020) - Papaioannou, Theo
ABSTRACT: Since the reconstruction of Joseph Schumpeter's view of innovation as a key factor of capitalist economic development and the neo-Schumpeterian formation of national innovation systems theory in the early 1990s, there has been an attempt to approach the emergence of new technological products and processes in evolutionary and institutional terms. However, much of this neo-evolutionism has positioned innovation as if it was a value-neutral process of supply and demand, taking place in a free market and having nothing to do with politics. I argue that such value neutrality is defended by some neo-Schumpeterian thinkers who take a socio-biological path to explaining innovation and technical change. In doing so, they abuse evolutionary theory to cloak the de facto strong role of political institutions and the state in innovation. Scholars of responsible research and innovation should unmask the public values involved in technological change and development.